2020
DOI: 10.3847/1538-4357/ab6d73
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Exponential Disk Galaxies in MOND

Abstract: The formation and evolution of galaxies is highly dependent on the dynamics of stars and gas, which is governed by the underlying law of gravity. To investigate how the formation and evolution of galaxies takes place in Milgromian gravity (MOND), we present full hydrodynamical simulations with the Phantom of Ramses (POR) code. These are the first-ever galaxy formation simulations done in MOND with detailed hydrodynamics, including star formation, stellar feedback, radiative transfer and supernovae. These model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 99 publications
4
55
0
Order By: Relevance
“…On the other hand, several recent studies found that many galaxies do not contain dark matter [44], [45]. This observation was considered in some studies where the galaxy formation was simulated using modified Newtonian dynamics without considering the dark matter [32]. Thus, it seems that there is no evidence or agreement on the existence or nature of the dark matter as well as it is not an essential element in some galaxies.…”
Section: Simulation Of Spiral Galaxymentioning
confidence: 99%
“…On the other hand, several recent studies found that many galaxies do not contain dark matter [44], [45]. This observation was considered in some studies where the galaxy formation was simulated using modified Newtonian dynamics without considering the dark matter [32]. Thus, it seems that there is no evidence or agreement on the existence or nature of the dark matter as well as it is not an essential element in some galaxies.…”
Section: Simulation Of Spiral Galaxymentioning
confidence: 99%
“…On the other hand, several recent studies report that many galaxies do not contain dark matter [34]. This scenario was used to inform galaxy formation simulations using modified Newtonian dynamics without considering the effects of dark matter [35]. Therefore, it seems that there is no evidence for (or agreement on) the existence or nature of dark matter, and it may be not an essential requirement for galaxy formation.…”
Section: Simulation Of Spiral Galaxymentioning
confidence: 99%
“…Several recent studies have reported that many galaxies do not contain dark matter [34]. This scenario was used to inform galaxy formation simulations using modified Newtonian dynamics without considering the effects of dark matter [35]. Therefore, it seems that there is no evidence for (or agreement on) the existence or nature of dark matter, and it may not be an essential requirement for galaxy formation.…”
Section: Simulation Of a Spiral Galaxymentioning
confidence: 99%